2021
DOI: 10.3389/fendo.2021.719843
|View full text |Cite
|
Sign up to set email alerts
|

3D Atlas of the Pituitary Gland of the Model Fish Medaka (Oryzias latipes)

Abstract: In vertebrates, the anterior pituitary plays a crucial role in regulating several essential physiological processes via the secretion of at least seven peptide hormones by different endocrine cell types. Comparative and comprehensive knowledge of the spatial distribution of those endocrine cell types is required to better understand their physiological functions. Using medaka as a model and several combinations of multi-color fluorescence in situ hybridization, we present the first 3D atlas revealing the gland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…Our data on the KEGG pathway enrichment analysis also indicated that, similar to zebrafish ( 67 ) and medaka ( 64 ), genes related to cell adhesion and extracellular matrix (ECM) are modulated in the pituitary during the start of puberty. This is in accordance with previous studies in mammals, in which components of the ECM were shown to modulate pituitary cell proliferation and hormone secretion ( 110 ).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our data on the KEGG pathway enrichment analysis also indicated that, similar to zebrafish ( 67 ) and medaka ( 64 ), genes related to cell adhesion and extracellular matrix (ECM) are modulated in the pituitary during the start of puberty. This is in accordance with previous studies in mammals, in which components of the ECM were shown to modulate pituitary cell proliferation and hormone secretion ( 110 ).…”
Section: Discussionmentioning
confidence: 66%
“…In both zebrafish ( 67 ) and medaka ( 64 ), but not in salmon (this RNAseq study analyzing samples collected within 1.5 weeks after starting the exposure to stimulatory conditions), lhb expression levels were also increased after the start of puberty. This discrepancy probably reflects the fact that those studies compared juvenile −immature− with adult −mature− stages while here, we compare two early stages of development, representing fish before and about to enter puberty, but prior to histologically visible signs of testis maturation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Unlike zebrafish, medaka have a sex-determining gene (Matsuda et al, 2002), and a high temperature (from 4–40 °C) and salinity (euryhaline species) tolerance (Sakamoto et al, 2001). Also, many genetic and anatomical tools, as well as protocols (Ager-Wick et al, 2018; Fontaine et al, 2018; Fontaine & Weltzien, 2019; Murata et al, 2019; Porazinski et al, 2010; Royan et al, 2020, 2021), have been developed in medaka to facilitate the study of its biology.…”
Section: Introductionmentioning
confidence: 99%